The necessity for tailoring seasonal climate forecast in Central America for urban and coastal areas, including physics and human dimensions - Alfaro Martínez, Eric J. (2014)
resumen de la presentación -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2014